Peran Self-Compassion Terhadap Flourishing Pada Mahasiswa Tahun Pertama - Abdullah, Annisa Aulia Rahma Hanum; Saleh, Airin Yustikarini (Fakultas Psikologi Universitas YARSI, 2025)
First-year university students are vulnerable to experiencing stress due to the transition to academic life, which can undermine their well-being or flourishing. Prior research has shown that greater self-compassion is associated with higher flourishing, but evidence among Indonesian first-year students remains limited. We hypothesized that self-compassion would be positively related to flourishing and to each of its components. A cross-sectional survey was conducted with 203 Indonesian first-year university students aged 18–20 years (M = 18.59, SD = 0.64), of whom 76.4% were female (N = 155). Participants completed the Skala Welas Diri (SWD) and the Indonesian adaptation of the PERMA-Profiler. Pearson correlations and multiple regression analyses were used to assess associations. Results showed that self-compassion was positively and significantly associated with overall flourishing (β = .512, p < .001) as well as with each of its dimensions (β = .344–.456, p < .001). These findings support the development of a self-compassion program as one option that universities can offer to first-year students to enhance their flourishing.